Land-use history drives functional divergence of native arbuscular mycorrhizal fungal communities in promoting maize growth in saline soils - Tianyi Niu; Youran Ma; Xuemin Jing; Haiyan Feng; Wei Fu; Zhipeng Hao; Xin Zhang; Songlin Wu; Baodong Chen (Applied Soil Ecology, 2026)

Experimental and Simulated Study on the Influence of Rock Separation on the Signal Response and Fracture Mechanism of Roof Strata - Weitao Yue; Enyuan Wang; Xiaojun Feng; Tingjiang Tan; Li Zhang; Dong Chen; Qiming Zhang (Rock Mechanics and Rock Engineering, 2026)

Deep Immunophenotyping Unravels the Double Negative T cells and PD-1-Mediated Inflammatory Exhaustion in Ankylosing Spondylitis - Lu Bai; Jian Gao; Yunyun Xu; Yuexin Yu; Jing Liu; Mathias Hochgerner; Hejian Zou; Xingdong Chen; Feng Qian; Hongjun He; Jiucun Wang (Phenomics, 2026)
Ankylosing spondylitis (AS) is a chronic, immune-mediated inflammatory disorder primarily affecting the axial skeleton. It is characterized by bony fusion and syndesmophyte formation of the spine, leading to compromised mobility, reduced quality of life and increased mortality. However, the underlying immune dysregulation in AS remains poorly understood. We comprehensively profiled the peripheral immune landscape of 30 patients with active AS, all of whom were TNF-α blocker-naïve, capturing the immune profile during the active disease phase without biologic interference. Using advanced 11-color flow cytometry and FlowSOM clustering, 584 immunophenotypes were analyzed in AS and 30 age-and sex-matched healthy controls, with emphasis on both cellular composition and functional characteristics. AS patients displayed a distinctive functional “activated-exhausted” immune phenotype, dominated by CD4 + CD28 + CD38 + PD-1 + T cells and HLA-DR + CD38 + CD4 − CD8 − double-negative (DN) T cells. DN T cells were significantly enriched in HLA-B27-positive patients, suggesting potential as a biomarker. Network analysis revealed seven central immune subsets associated with active disease, while functional assessment demonstrated impaired CD95 + CD8 + T cell apoptosis and disrupted B-cell maturation. These findings provide a detailed functional immune map of biologic-naïve active AS, offering novel mechanistic insights and identifying candidate biomarkers for precision intervention.

Phosphogypsum-induced adaptive restructuring of bacterial communities in vegetation capping strategies: From sulfur cycling to carbon fixation in vegetation - Jiaqi Tan; Zhen Wang; Yingdong Chen; Chaomeng Zhang; Delong Meng; Wenchao Li; J. Viridiana García Meza; Shaoxian Song; Ling Xia (Applied Soil Ecology, 2026)

Seedling mycorrhization increases maize yield without altering soil properties: A field study - Rongbin Yin; Zhipeng Hao; Youran Ma; Wei Fu; Hui Wu; Fei Xue; Mengyao Sun; Weiqi Wang; Xin Zhang; Baodong Chen (Applied Soil Ecology, 2026)

Long-term green manuring increases phosphorus availability in soil by modifying microbial functional genes and enzyme activities - Xiaodong Chen; Yuan Wang; Bin Guo; Junli Liu; Gaoyang Qiu; Kuzyakov Yakov; Hua Li (Applied Soil Ecology, 2025)

Inorganic amendment can delay the degradation of organic amendment by enhancing its resistance and mitigating microbial activities in saline–alkali soils - Shan Li; Yuanyuan Yao; Congling Zhou; Songyuan Wang; Zihan Liu; Yan Liu; Junyin Li; Guiwei Wang; Bin Gao; Dongdong Cheng; Yuechao Yang (Applied Soil Ecology, 2025)

Ecoenzymatic stoichiometry reveals the exacerbation of microbial C and N limitations by moss crusts in degraded karst ecosystems - Minghao Deng; Jiaojiao Wu; Xin Zhao; Dong Chen; Guanting Guo; Mingzhong Long; Qimei Wu; Run Liu; Xiaona Li (Applied Soil Ecology, 2025)

Contrasting effects of litter and root removals on soil N2O emissions of an evergreen broadleaved forest in southeastern China - Lei Zhang; Weisheng Lin; Jordi Sardans; Enlan Xu; Dafeng Hui; Xiaofei Liu; Jinsong Wang; Shidong Chen; Jianfen Guo; Josep Peñuelas; Yusheng Yang (Applied Soil Ecology, 2025)

The dominance of K-strategy microbes enhances the potential of soil carbon decomposition under long-term warming - Yanli Gao; Jiacong Zhou; Teng-chiu Lin; Yiqing Li; Quanxin Zeng; Shidong Chen; Decheng Xiong; Qiufang Zhang; Zhijie Yang; Yusheng Yang (Applied Soil Ecology, 2025)